Trigeminal neuralgia secondary to arteriovenous malformation in the brainstem: a case report and a brief review - Severo Bem Junior, Luiz; Fechine de Alencar Neto, Joaquim; Augusto Lustosa Nogueira, Júlio; Sena Almeida , Nivaldo; Rocha Cirne de Azevedo Filho, Hildo (Headache Medicine, 2022)
Trigeminal neuralgia, a condition characterized by high intensity, paroxysmal and unilateral pain, can be characterized as secondary when associated with conditions such as multiple sclerosis and tumors. However, among these secondary cases, there are also arteriovenous malformations, characterized by a nidus mass of vessels separated by parts of sclerotic tissues, responsible for a small portion of the neuralgias of the trigeminal nerve. The case report described is of a 54-year-old male patient who has a brainstem AVM and refers to lancing and paroxysmal pain in the right hemiface in the territories of V2 and V3 after feeding and brushing the teeth. The treatment of this patient was done from the insertion of a balloon from the foramen ovale, accessed by the Meckel fossa and the trigeminal ganglion. The literature review demonstrated, from the analysis of gender, age, vascularization, localization and treatments of reports of TGN secondary to brainstem AVM, the reduced number of cases described.